Insights into the occurrence of phylosymbiosis and co-phylogeny in the holobionts of octocorals from the Mediterranean Sea and Red Sea - C. Prioux; C. Ferrier-Pages; J. Deter; R. Tignat-Perrier; A. Guilbert; L. Ballesta; D. Allemand; J. A. J. M. van de Water (Animal Microbiome)
Abstract Background Corals are the foundational species of coral reefs and coralligenous ecosystems. Their success has been linked to symbioses with microorganisms, and a coral host and its symbionts are therefore considered a single entity, called the holobiont. This suggests that there may be evolutionary links between corals and their microbiomes. While there is evidence of phylosymbiosis in scleractinian hexacorals, little is known about the holobionts of Alcyonacean octocorals. Results 16S rRNA gene amplicon sequencing revealed differences in the diversity and composition of bacterial communities associated with octocorals collected from the mesophotic zones of the Mediterranean and Red Seas. The low diversity and consistent dominance of Endozoicomonadaceae and/or Spirochaetaceae in the bacterial communities of Mediterranean octocorals suggest that these corals may have a shared evolutionary history with their microbiota. Phylosymbiotic signals were indeed detected and cophylogeny in associations between several bacterial strains, particularly those belonging to Endozoicomonadaceae or Spirochaetaceae, and coral species were identified. Conversely, phylosymbiotic patterns were not evident in Red Sea octocorals, likely due to the high bacterial taxonomic diversity in their microbiota, but cophylogeny in associations between certain coral and bacterial species was observed. Noteworthy were the associations with Endozoicomonadaceae, suggesting a plausible evolutionary link that warrants further investigations to uncover potential underlying patterns. Conclusions Overall, our findings emphasize the importance of Endozoicomonadaceae and Spirochaetaceae in coral symbiosis and the significance of exploring host-microbiome interactions in mesophotic ecosystems for a comprehensive understanding of coral-microbiome evolutionary history.